KOMUNIKASI EFEKTIF DALAM DUNIA PENDIDIKAN - Wisman, Yossita (Jurnal Nomosleca, 2017)
Abstract Learning process (learning) is a change that is relatively fixed in behaving. so, the learning process puts one person from one ability or ability status to another skill / ability. The process of communication in the delivery of a goal is more than simply channeling thoughts or ideas and intentions orally or in writing. The communication method consists of: (1) informative communiation, a message delivered to a person / a number of people about the new things he / she knows. (2) persuasive communication (persuasive communication) is the process of influencing one's attitude, outlook, or behavior in the form of persuasive and inviting activities, so that he performs with his own consciousness. (3) instructive / coercive communication, are: communications that contain threats / penance in the nature of coercion, so that the targeted people do something forced, for fear of the consequences.Keywords : learning,ability,attention,interest,communicationDOI : http://doi.org/10.26905/nomosleca.v3i2.2039